Influence of nitrogen source and concentrations on wheat growth and production inside "Lunar Palace-1". (March 2018) - Dong, Chen; Chu, Zhengpei; Wang, Minjuan; Qin, Youcai; Yi, Zhihao; Liu, Hong; Fu, Yuming
Abstract: Minimizing nitrogen (N) consumption and maximizing crop productivity are major challenges to growing plants in Bioregenerative Life Support System (BLSS) for future long-term space mission. Plants cultivated in the controlled environments are sensitive to the low recyclable N (such as from the urine). The purpose of this study is to investigate the effects of nitrogen fertilizer (NH4 + -N and NO3 − -N) disturbance on growth, photosynthetic efficiency, antioxidant defence systems and biomass yield and quality of wheat ( Triticum aestivum L.) cultivars during ontogenesis. Experiments were divided into 4 controlled groups, Ⅰ: NO3 − -N: NH4 + -N = 7:1 mmol L −1 ; Ⅱ: NO3 − -N: NH4 + -N = 14:0.5 mmol L −1 ; Ⅲ: NO3 − -N: NH4 + -N = 7:0.5 mmol L −1 and CK: NO3 − -N: NH4 + -N = 14:1 mmol L −1, and other salt concentrations were the same. The results showed that heading and flowering stages in spring wheat are sensitive to low N concentration, especially NO3 − -N in group Ⅰ and Ⅲ. NO3 − is better to root growth than to shoot growth. The plants were spindling and the output was lower 21.3% when spring wheat was in low N concentration solution. Meanwhile, photosynthetic rate of low N concentrations is worse than that of CK. The soluble sugar content of the edible part of wheat plants is influenced with NO3 − : NH4 + ratio. In addition, when N concentration was lowest in group Ⅲ, the lignin content decreased to 2.58%, which was more beneficial to recycle substances in the processes of the environment regeneration. Highlights: NO3 − and NH4 + concentration and ratio have significant effects on wheat root and shoot growth. Soluble sugar content of wheat edible part is affected by NO3 − : NH4 + ratio. When heading and flowering, wheat is sensitive to N concentration.